Biological Activities of Extract from Watermelon rind Citrullus Lanatus (Thunb.) Matsum and Nakai - Satsue, Sathaporn; Suksai, Wilailak; Thapphasaraphong, Suthasinee (The Journal of Chulabhorn Royal Academy, 2023)
Background: Watermelon rind is a waste that is not utilized, contains important groups of vitamin C, fiber, and citrulline, which is an antioxidant and has a significant benefit to the human body. Objectives: The aim of this study was to investigate the biological activities of the 85% ethanolic extracts of watermelon rind (Citrullus Lanatus (Thunb.) Matsum and Nakai) Methods: These study were in vitro test. The total phenolic content and antioxidant activity were evaluated according to DPPH, ABTS and FRAP assays. Human Forehead Fibroblast Cells (HFF) of cell proliferation by MTT assay and collagen content analysis by Hydroxyproline Assay from cell culture media with extracts. Results: The results showed that 85% ethanolic extracts of watermelon rind (Citrullus Lanatus (Thunb.) Matsum and Nakai) had total phenolic content was 32.60 ± 0.84 µg GAE/mg extracts, antioxidant activities by DPPH and ABTS calculated in IC 50 833.40 ± 2.46, 1655.48 ± 0.05 µg/ml, respectively. The FRAP value was 0.23 ± 0.03 mM Fe (II)/mg. The HFF cell viability increased with increasing concentration of watermelon rind extract at 62.5-500 µg/ml but cell viability will be decreased at than 500 µg / ml. The highest collagen content was 256.79±24.69 µg/ml and concentration at 1000 µg/ml showed the highest collagen Conclusions: The extracts of watermelon rind (Citrullus Lanatus (Thunb.) Matsum and Nakai) had total phenolic compounds, antioxidant activity and collagen stimulating activity in HFF cell culture, therefore these extracts the develop for cosmeceutical products in the future.